Organic solutes in coconut palm seedlings under water and salt stresses - Silva,Alexandre R. A. da (2016)
ABSTRACT The objective of this study was to investigate the biochemical mechanisms associated with isolated and/or concurrent actions of drought and soil salinity in seedlings of coconut tree, through the accumulation of organic solutes (soluble carbohydrates, soluble amino N and free proline) in leaves and roots. The experiment, conducted in a protected environment, in Fortaleza, Brazil, in a randomized block design, in a split-plot arrangement, evaluated the effects of different levels of water stress (plots) by imposing distinct percentages of replacement of water losses through crop potential evapotranspiration - ETpc (20, 40, 60, 80 and 100%), associated with subplots consisting of increasing levels of soil salinity in saturation extract (1.72, 6.25, 25.80 and 40.70 dS m-1) provided by the soils collected in the Irrigated Perimeter of Morada Nova. Salinity did not change the concentration of organic solutes; however, there were increases in leaf and root levels of free proline in response to water stress, which contributes to the osmoregulation and/or osmoprotection of the species under adverse conditions of water supply.